Effects of country animosity of angry Koreans on Japan: A focus on export regulation on Korea - Sun, Lili; Jun, Jong-Woo (Frontiers in Psychology, 2022)
Nowadays, Korea and Japan are in conflict arising from export restrictions launched by Japan on Korea, which have provoked a boycott of Japanese products in Korea, and even tourism to Japan. Animosity performs a momentous role in the context of crisis management communication. Hence, the paper aims to investigate factors impacting on boycott intention to visit Japan, with economic animosity being a principal mediating variable, whose antecedents and consequences have been probed into. A total of 333 respondents’ survey data were collected, and analyzed via SEM for verification of the research hypotheses. The findings manifest that ethnic identity engenders a significant direct positive effect on economic animosity and boycott news, and boycott news significantly positively affects economic animosity; boycott news serves as the mediating role between ethnic identity and economic animosity. Additionally, it has been demonstrated that economic animosity exerts a significant positive impact on boycott visit intention, economic animosity negatively affects Japanese government trust, and Japanese government trust negatively bears upon boycott visit intention; Japanese government trust mediates between economic animosity and boycott intention to visit Japan. Consequently, the research makes contributions to furnishing empirical evidence for influencing factors of boycott visit intention, and enriching the literature on the antecedents and consequences of animosity.